2020
DOI: 10.3389/fgene.2020.00833
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diagnosis of Familial Hypercholesterolemia in Asia

Abstract: Familial hypercholesterolemia (FH) is a common genetic disease with an incidence of about 1 in 200-500 individuals. Genetic mutations markedly elevate low-density lipoprotein cholesterol and atherosclerotic cardiovascular disease (ASCVD) in FH patients. With advances in clinical diagnosis and genetic testing, more genetic mutations have been detected, including those in low-density lipoprotein receptor (LDLR), apolipoprotein B (APOB), proprotein convertase subtilisin/kexin type 9 (PCSK9), and so on. Globally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
10
0
4
Order By: Relevance
“…FH includes homozygous and heterozygous types that have different symptoms, risks, and treatments. The incidence of FH is approximately 1 in 200–500 individuals and confers a significant risk for premature cardiovascular disease (CVD) [ 3 ]. Study has reported that the risk of premature CHD is elevated approximately 20-fold in young untreated heterozygous FH men and that homozygous FH patients typically develop CHD by the second decade of life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…FH includes homozygous and heterozygous types that have different symptoms, risks, and treatments. The incidence of FH is approximately 1 in 200–500 individuals and confers a significant risk for premature cardiovascular disease (CVD) [ 3 ]. Study has reported that the risk of premature CHD is elevated approximately 20-fold in young untreated heterozygous FH men and that homozygous FH patients typically develop CHD by the second decade of life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA was isolated from 10 mL of venous blood recently been reported in about 1% of FH cases in Caucasians 4) and 8% in Japanese 5) , but has not been reported in Taiwanese patients 6) . Identification of patients with FH can be achieved by clinical diagnosis, i.e., by examination of personal and family history.…”
Section: Dna Extractionmentioning
confidence: 99%
“…The criteria for the clinical diagnosis of FH have been established and reported by the 2017 Taiwan Lipid Guidelines, a modification of the Dutch Lipid Clinic Network Score (DLCNS) for FH in Taiwan 7) . The diagnosis of FH is dependent on the total scores and can be definite (when the score is more than 8), probable (6)(7)(8), or possible (3)(4)(5).…”
Section: Dna Extractionmentioning
confidence: 99%
“…APOC1 is a member of the apolipoprotein family that ACTS not only to transport lipids and stabilize the lipoprotein structure but also to regulate pathological processes including diabetes, Alzheimer's and inflammation. [11][12][13][14] In recent years, some studies have found that ApoA1, 15,16 ApoB, [17][18][19] ApoE 20,21 and other apolipoproteins 22 are abnormally expressed in tumors and are related to the prognosis of patients. Therefore, the role of apolipoprotein family in the occurrence and development of tumors has attracted more attention.…”
Section: Introductionmentioning
confidence: 99%